Perancangan Komik dari Buku Filosofi Teras oleh Henry Manampiring Sebagai Media Informasi Filsafat Stoikisme untuk Generasi Z - Hadiwijoyo, Rio; Crisdi, Lucas (AMARASI: JURNAL DESAIN KOMUNIKASI VISUAL, 2024)
In this modern era, Indonesian people easily feel worried and anxious about life. This is also triggered by the flood of easily accessible information which makes people easily anxious. This excessive anxiety can disrupt an individual's quality of life. Therefore, a strong outlook on life is needed to fight it all. Teras Philosophy is a book written by Henry Manampiring, discussing the philosophy of Stoicism which is more than 2000 years old. One of the philosophies of this view is the importance of distinguishing between things that are within our control and outside our control. However, the philosophy of Stoicism is still a topic that is not common among the public, so there is a need for other media to provide information regarding the understanding of this philosophy. One of the media that can be used is visual media so that it can be easily digested by the public. Based on that, it is necessary to design visual media to increase information about the philosophy of Stoicism. In this final work, the author uses qualitative research methods to obtain the necessary data. The design of this comic aims to disseminate information about the philosophy of Stoicism. As a result of this research, the author created comics that are interesting and acceptable to Generation Z. There are also print and digital media promotional designs in the form of posters, x-banners, and digital content for social media. In adapting the book Teras Philosophy, comics can be serialized to cover all the chapters in the book. So the comic work will be more complete and complete.